HIGH-MOLECULAR-WEIGHT HYALURONAN—A POTENTIAL ADJUVANT TO FLUID RESUSCITATION IN ABDOMINAL SEPSIS?. Issue 5 (22nd May 2023) - Barrueta Tenhunen, Annelie; van der Heijden, Jaap; Dogné, Sophie; Flamion, Bruno; Weigl, Wojciech; Frithiof, Robert; Skorup, Paul; Larsson, Anders; Larsson, Anders; Tenhunen, Jyrki
ABSTRACT: While fluid resuscitation is fundamental in the treatment of sepsis-induced tissue hypoperfusion, a sustained positive fluid balance is associated with excess mortality. Hyaluronan, an endogenous glycosaminoglycan with high affinity to water, has not been tested previously as adjuvant to fluid resuscitation in sepsis. In a prospective, parallel-grouped, blinded model of porcine peritonitis sepsis, we randomized animals to intervention with adjuvant hyaluronan (add-on to standard therapy, n = 8) or 0.9% saline (n = 8). After the onset of hemodynamic instability, the animals received an initial bolus of 0.1% hyaluronan (1 mg/kg/10 min) or placebo (0.9% saline) followed by a continuous infusion of 0.1% hyaluronan (1 mg/kg/h) or saline during the experiment. We hypothesized that the administration of hyaluronan would reduce the volume of fluid administered (aiming at stroke volume variation <13%) and/or attenuate the inflammatory reaction. Total volumes of intravenous fluids infused were 17.5 ± 11 versus 19.0 ± 7 mL/kg/h in intervention and control groups, respectively ( P = 0.442). Plasma IL-6 increased to 2, 450 (1, 420–6, 890) pg/mL and 3, 690 (1, 410–11, 960) pg/mL (18 hours of resuscitation) in the intervention and control groups (nonsignificant). The intervention counteracted the increase in proportion of fragmented hyaluronan associated with peritonitis sepsis (mean peak elution fraction [18 hours of resuscitation] intervention group: 16.8 ± 0.9 versus control group: 17.9 ± 0.6 [ P = 0.031]). In conclusion, hyaluronan did not reduce the volume needed for fluid resuscitation or decrease the inflammatory reaction, even though it counterbalanced the peritonitis-induced shift toward increased proportion of fragmented hyaluronan.